Psychotherapy of Existential Guilt as a Means of Preserving the Psychological Health of the Individual - Terletska, Larysa (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The article presents the results of research into the concept of existential guilt in foreign psychology. Currently, the problem of experiencing existential guilt occupies one of the central places in psychological research. This is due to the fact that in extreme life situations (war, pandemic, economic and social danger, etc.), a person’s experience of a sense of guilt, and especially existential guilt, increases sharply. The purpose of the study: to reveal the meaning of the concept of guilt and its types, the peculiarities of the individual’s experience of existential guilt. Methods. To solve the tasks, the work used methods of theoretical and empirical research: a) theoretical methods analysis, classification, types, generalization made it possible to scientifically and theoretically substantiate the data we received; b) empirical methods - diagnosis of self-actualization of students, content analysis of the experience of guilt in students with a high and low level of self-actualization of the personality. Results. Analyzed concepts: guilt, fear, anxiety, existential guilt, shame. A comparison of the emotions of shame and guilt shows that the feeling of shame often activates defense mechanisms, leads to distancing from the situation, while the feeling of guilt causes constructive responses and a desire to correct the situation; guilt is positively related to empathy, and shame is inversely related to it; finally, the feeling of shame can lead to psychological distress - depression, anxiety, obsessive states, low self-esteem, eating disorders, etc., while with regard to the feeling of guilt, similar connections have not been recorded Conclusion. The general conclusion is that the feeling of guilt is positive from the point of view that it not only keeps a person within a moral framework, but also motivates to act correctly and strive to correct the situation.